Genome-Wide Identification and Expression Analysis of PkNRT Gene Family in Korean Pine (Pinus koraiensis) - Xinyu Zhao; Haibo Wu; Boyang Li; Pengyang Wang; Peng Zhang; Hailong Shen; Jianfei Yang (Plants)
The utilization of nitrogen (N) is crucial for the optimal growth and development of plants. As the dominant form of nitrogen in temperate soil, nitrate (NO3−) is absorbed from the soil and redistributed to other organs through NO3− transporters (NRTs). Therefore, exploration of the role of NRTs in response to various NO3− conditions is crucial for improving N utilization efficiency (NUE). Here, we present a comprehensive genome-wide analysis and characterization of the NRT gene family in Korean pine, an invaluable tree species cultivated extensively in northeastern China. A total of 76 PkNRTs were identified in Korean pine and further divided into three subfamilies (NRT1/NPF, NRT2, and NRT3) based on phylogenetic analysis. All PkNRTs were distributed on 11 chromosomes, with multiple tandem duplications observed. The tissue-specific expression analysis indicated that most PkNRTs showed differential expression in six vegetative tissues. Furthermore, a significantly greater number of lateral roots was observed in seedlings under nitrogen-deficient conditions, accompanied by an increase in both total root biomass and root length. The temporal expression profiles of 16 PkNRTs in seedling roots revealed that four PkNRTs, PkNPF5.6, PkNPF5.13, PkNPF6.1, and PkNPF6.2, exhibited significantly upregulated expression under the NO3− deficiency condition, whereas robust induction was observed for PkNPF1.1, PkNRT2.6, and PkNRT3.3 upon the NO3− sufficiency condition. The expression patterns of the PkNRTs suggest their potential diverse roles as key participants in root NO3− uptake under varying NO3− conditions during root development. These findings would provide a theoretical foundation for further investigations into the functions of PkNRTs in Korean pine.